PENGARUH MOTIVASI INTRINSIK DAN SEMANGAT KERJA TERHADAP KINERJA KARYAWAN DI KANTOR DESA BURUAN, BLAHBATUH GIANYAR - Ni Kadek Dwika; Ida Bagus Made Widiadnyana; Sapta Rini Widyawati (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2022)
Performance is the work results that produced both in terms of quality and quantity of work and can be accounted for in accordance with its role in the organization or company. Work results are accompanied by abilities, accuracy, and skills to complete the work within a certain period of time. The purpose of this study was to determine the effect of intrinsic motivation and morale on employee performance. The research was conducted at the Buruan village office, which is located at Blahbatuh, Gianyar. The object of this research is the field of human resource management, namely intrinsic motivation and work spirit on employee performance. The population in this study were all 35 employees who worked at the Buruan village office, consisting of 20 men and 15 women. The sampling method used in this study is the saturated sampling method, in which all members of the population are sampled, with a total of 35 samples. The data analysis technique used in this research is multiple linear regression analysis. The results of this study are intrinsic motivation has a positive and significant increase on employee performance, as well as employee morale at the Buruan village office, Blahbatuh Gianyar.